2009
DOI: 10.1002/chem.200900231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biophysical Studies on 35‐Deoxy Amphotericin B Methyl Ester

Abstract: The use of molecular editing in the elucidation of the mechanism of action of amphotericin B is presented. A modular strategy for the synthesis of amphotericin B and its designed analogues is developed, which relies on an efficient gram-scale synthesis of various subunits of amphotericin B. A novel method for the coupling of the mycosamine to the aglycone was identified. The implementation of the approach has enabled the preparation of 35-deoxy amphotericin B methyl ester. Investigation of the antifungal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 115 publications
0
26
0
1
Order By: Relevance
“…1C, Right), two molecular aggregates, each spanning one half of the lipid bilayer, are united into a membrane-spanning channel via hydrogen bonds between the C35 hydroxyl groups on AmB molecules in opposing leaflets (28). Supporting an important role for this hydroxyl group in channel formation, in vitro studies in model liposomes demonstrated that a doubly modified derivative of AmB, in which the C41 carboxylic acid is protected as a methyl ester and the C35 hydroxyl group is removed, caused only weak potassium efflux at high concentration (10 μM) and no efflux at low concentration (1 μM) (29). Our own studies suggested that the weak efflux observed in the former case was likely an artifact of the relatively sensitive nature toward membrane permeabilization of liposomes versus live yeast cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1C, Right), two molecular aggregates, each spanning one half of the lipid bilayer, are united into a membrane-spanning channel via hydrogen bonds between the C35 hydroxyl groups on AmB molecules in opposing leaflets (28). Supporting an important role for this hydroxyl group in channel formation, in vitro studies in model liposomes demonstrated that a doubly modified derivative of AmB, in which the C41 carboxylic acid is protected as a methyl ester and the C35 hydroxyl group is removed, caused only weak potassium efflux at high concentration (10 μM) and no efflux at low concentration (1 μM) (29). Our own studies suggested that the weak efflux observed in the former case was likely an artifact of the relatively sensitive nature toward membrane permeabilization of liposomes versus live yeast cells (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The synthesis of polyene macrolides is challenging because of the sensitivity of these molecules to light, oxygen, and many organic reagents, including the basic and/or acidic conditions often required at the end of a pathway to remove various protective groups. These sensitivities can be magnified considerably when specific functional groups have been deleted from the polyene macrolide skeleton, which has previously precluded the synthesis of some targeted AmB derivatives, including C35deOAmB (29). To improve the efficiency and flexibility with which such complex small molecules can be prepared, we have recently developed a simple and modular synthesis strategy, analogous to iterative peptide coupling, in which building blocks having all of the required functional groups preinstalled in the correct oxidation states and with the desired stereochemical relationships are sequentially linked via iterative application of one mild reaction (30)(31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in vitro experiments that involve modifying the constitution of lipid bilayers are challenging to translate into living yeast cells. Overcoming these limitations, we have demonstrated an experimental strategy based on the synthesisenabled deletion of functional groups from the polyene macrolide skeleton and determination of the biological and biophysical consequences (49,64). In this report, we have harnessed a highly efficient and flexible degradative synthesis pathway to prepare large quantities of three functional group-deficient derivatives of AmB.…”
Section: Discussionmentioning
confidence: 99%
“…The polyol sections of the antibiotics make up the channel's interior. Comparing the ion‐channel‐forming propensities of amphotericin B ( 1 ) with designed analogues thereof14 supported this concept and revealed three facts: 1) Pairs of channels interact with one another longitudinally so that they span the width of the membrane,14a 2) the sugar moiety reinforces the binding of the sterol by a hydrogen bridge,14b,14d,14e and 3) the carboxylic acid moiety is not essential for antifungal activity 14b,14e. Smaller‐sized polyol,polyene antibiotics like pimaricin ( 4 ) and rimocidin ( 5 ) do not make cell membranes permeable for ions 15.…”
Section: Introductionmentioning
confidence: 92%